Pengaruh persepsi kemudahan, risiko dan manfaat terhadap keputusan nasabah menggunakan mobile banking BRI - Adria Yudi Kurniaputra; Mochamad Nurhadi (STIE Perbanas Surabaya, 2018)
The study purposes to examine the perceived convenience, risk and benefi ts toward decision to use BRI Mobile Banking in Surabaya. The study is using SPSS Program. The population used in this study is all customers of the Bank BRI in Surabaya, especially in Kaliasin, Kusuma Bangsa and Jemursari branches. The data were collected using questionnaire. To conduct this study, the data were fi nally taken with 80 respondents. This research method used is quantitative. Multiple linear regression analysis used in this study to analyze the data statistically. The results show that perceived convenience and benefi ts affects positive signifi cant the decision to use mobile banking BRI in Surabaya, while the perceived risk is affects not signifi cant the decision to use mobile banking BRI in Surabaya.